Modeling the predicted suitable habitat distribution of Javan hawk-eagle Nisaetus bartelsi in the Java Island, Indonesia - ILYAS NURSAMSI; RUHYAT PARTASASMITA; NURVITA CUNDANINGSIH; HASNA SILMI RAMADHANI (Biodiversitas Journal of Biological Diversity, 2018)
Nursamsi I, Partasasmita R, Cundaningsih N, Ramadhani HS. 2018. Modeling the predicted suitable habitat distribution of Javan hawk-eagle Nisaetus bartelsi in the Java Island, Indonesia. Biodiversitas 19: 1539-1551. Javan hawk-eagle (Nisaetus bartelsi) is an endemic raptor of Java Island. The conservation status of Javan hawk-eagle (JHE) according to IUCN is endangered (EN) and included in CITES Appendix II list, and this species is also protected by the Indonesian government law based on act no. 5, year 1990. The position of Javan hawk-eagle as a top predator is now very threatened by habitat fragmentation, wildlife trade, and the declining quality of its habitat. The primary purpose of this study was to give preliminary information about the distribution of predicted suitable habitat for JHE as a means of finding potential releasing sites, as an evaluation for habitat protection, and even as an option for the development of new JHE protected areas. However, mapping the spatial distribution of potential habitat for JHE using terrestrial survey is problematic because it requires enormous time, fund, and human resources. The most possible approach is by using Ecological Niche Modeling (ENM)/species distribution modeling (SDM). In this study, modeling exercise was conducted by using a maximum entropy method as an adaptation from Maxent software ver. 3.4.1, with the utilization of JHE-nest coordinate data and 16 environmental variables datasets as the main input. The predicted suitable habitat distribution map has shown a good match with historical and present records of JHE and has fairly succeeded in capturing a wide range of habitat patches from tiny spots to quite large suitable habitat. Modeling results also showed that altitude, annual mean temperature, and two types of land cover (closed shrub, and forest area) are considered to be most important variables affecting the distribution of potential habitat for JHE. Moreover, about 17.77% (23,209 km2) area of Java Island has been projected to be suitable for Havan Hawk-Eagle's habitat, which mostly spread in mountainous areas while also appear in several lowland areas. This study suggests the importance of topographic, climatic, and land cover as pivotal predictors in determining the suitability of habitat for JHE. This study also shows that the modeling results have a good match with the historical records of JHE across the island, which suggests the overall accuracy of the model.